2020
DOI: 10.1002/path.5368
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome subunit β5i regulates diet‐induced atherosclerosis through altering MERTK‐mediated efferocytosis in Apoe knockout mice

Abstract: The immunoproteasome contains three catalytic subunits (β1i, β2i and β5i) that are important modulators of immune cell homeostasis. A previous study showed a correlation between β5i and human atherosclerotic plaque instability; however, the causative role of β5i in atherosclerosis and the underlying mechanisms remain unknown. Here we explored this issue in apolipoprotein E (Apoe) knockout (eKO) mice with genetic deletion or pharmacological inhibition of β5i. We found that β5i expression was upregulated in lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…These studies indicated that LMP10 targets NF-κB activation possibly through PTEN/AKT/IKK signaling. Interestingly, our recent study on experimental atherosclerosis also supports LMP7mediated transcriptional regulation of efferocytosis through oxidized LDL-induced IκBα degradation and subsequent NF-κB activation (Liao et al, 2020a). In the current study, we observed that oxidized LDL-induced degradation of IκBα and activation of NF-κB pathway was also reduced in LMP10deleted macrophages (Figures 6F,G), suggesting that LMP10 deletion inhibited NF-κB activation partially through blocking IκBα degradation.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…These studies indicated that LMP10 targets NF-κB activation possibly through PTEN/AKT/IKK signaling. Interestingly, our recent study on experimental atherosclerosis also supports LMP7mediated transcriptional regulation of efferocytosis through oxidized LDL-induced IκBα degradation and subsequent NF-κB activation (Liao et al, 2020a). In the current study, we observed that oxidized LDL-induced degradation of IκBα and activation of NF-κB pathway was also reduced in LMP10deleted macrophages (Figures 6F,G), suggesting that LMP10 deletion inhibited NF-κB activation partially through blocking IκBα degradation.…”
Section: Discussionmentioning
confidence: 73%
“…Previous research has shown that LMP7 expression is increased in the shoulder areas of symptomatic carotid plaques and in correlation with inflammatory cell infiltration, but the causative roles and potential mechanisms of immunoproteasomes in atherosclerosis remain unclear (Herrmann et al, 2012). Recently, we demonstrated in ApoE ko mice that ATD feeding significantly induced LMP7 expression in plaque macrophages, and that genetic and pharmaceutical inhibition of LMP7 attenuated diet-induced atherosclerosis (Liao et al, 2020a). Furthermore, we identified in isolated macrophages that LMP7-mediated regulation of atherosclerosis was associated with efferocytosis of apoptotic cells during foam cell formation (Liao et al, 2020a).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies from our group have showed that PYR-41 is able to prevent the degradation of a wide range of target proteins, such as IκBα and MKP-1 [15,22]. Among them, IκBα is an inhibitory protein for NF-κB signaling pathway, which is known to play a critical role in regulating inflammatory cytokine and NADPH oxidase expression during cardiac remodeling and atherosclerosis [15,23]. Interestingly, our recent data indicate that PYR-41 might suppress inflammation and oxidative stress possibly through stabilization of IκBα and inhibition of Journal of Immunology Research NF-κB activation in several cell and disease models [15,22].…”
Section: Discussionmentioning
confidence: 99%